Registration of dynamic contrast‐enhanced MRI of the common carotid artery using a fixed‐frame template‐based squared‐difference method. Issue 4 (7th October 2013) - Ramachandran, Sarayu; Calcagno, Claudia; Mani, Venkatesh; Robson, Philip M.; Fayad, Zahi A.
Abstract : Purpose: This study examines template‐based squared‐difference registration for motion correction in dynamic contrast‐enhanced (DCE) MRI studies of the carotid artery wall and compares the results of fixed‐frame template‐based registration with a previously proposed consecutive‐frame registration method. Materials and Methods: Ten T1‐weighted black‐blood, turbo spin‐echo DCE‐MRI studies of the carotid artery wall were used to test template‐based squared‐difference registration. An intermediate image from each series was selected as the fixed‐frame template for registration. Squared‐difference minimization was used to align each image and template. Time‐intensity curves generated from data aligned with template‐based squared‐difference registration were compared with gold standard curves created by drawing regions of interest on each image in the series. The results were also compared with unregistered data and data after consecutive‐frame squared‐difference registration. Results: An analysis of variance test of root mean‐square error values between gold standard curve and curves from unregistered data and data registered with consecutive‐frame and fixed‐frame template‐based methods was significant ( P < 0.005) with template‐based squared‐difference registration producing curves that most closely matched the gold standard. Conclusion: A fixed‐frame template‐based squared‐difference registration method was proposed and validated for alignment of DCE‐MRI of carotid arteries.J. Magn. Reson. Imaging 2014;39:1017–1017. ©2013 Wiley Periodicals, Inc.